Identification of circular RNAs expression pattern in caprine fetal fibroblast cells exposed to a chronic non-cytotoxic dose of graphene oxide-silver nanoparticle nanocomposites - Yuan, Yu-Guo; Xing, Yi-Tian; Liu, Song-Zi; Li, Ling; Reza, Abu Musa Md Talimur; Cai, He-Qing; Wang, Jia-Lin; Wu, Pengfei; Zhong, Ping; Kong, Il-Keun (Frontiers in Bioengineering and Biotechnology, 2023)
The increasing use of graphene oxide-silver nanoparticle nanocomposites (GO-AgNPs) in biomedical sciences and research also increases the chances of human and animal exposure to its chronic non-toxic doses. Exposure of the maternal environment to AgNPs-related nanomaterials during pregnancy may result in the health problem of the dam, fetus and offspring. However, the available information is truly little for profound understanding of the effect of low-dose chronic exposure to GO-AgNPs on the epigenetic modification of the organism. In this research, we have investigated the impact of non-toxic doses of GO-AgNPs (0.5 µg/mL for 10 weeks, this dose does not interfere with cell viability and ROS level) on the differential expression of circular RNAs (circRNAs) in caprine fetal fibroblast cells (CFFCs). In addition, using bioinformatics tools we have predicted the functions of those differentially expressed circRNAs on CFFCs. Furthermore, we have validated the expression of ten circRNAs using quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) to ensure the reliability of the sequencing data. The results showed that the differentially expressed circRNAs potentially regulates the GO-AgNPs induced epigenetic toxicity through a regulatory network consisted of circRNAs, miRNAs and messenger RNAs (mRNAs). Therefore, the inclusion of epigenetics approaches is essential to assess the biosafety level of GO-AgNPs nanomaterials.